ANALYZING HIGHER ORDER THINKING SKILLS (HOTS) QUESTIONS OF READING ESSAY TASK IN SENIOR HIGH SCHOOL ENGLISH TEXTBOOK - Maziyyatus Shalihah; Dzul Fikri; Mutmainnah Mustofa; Dwi Fita Heriyawati (Language-Edu, 2022)
English textbook especially senior high school must consist of qualified English reading tasks in order to boost studentsâ€™ english skills by being trained with reading and vocabulary mastery at once. This drives the researcher to do a qualitative with one research questions to fiugure out; â€œhow is Higher Order Thinking Skills (HOTS) in essay reading exercises distributed in English SMK/ MAK textbook for X, XI, and XII grades?â€. The researcher selected senior high school English textbook for X, XI, and XII grades by BUMI AKSARA. Analysis steps were sequentially completed started from textbook observation, question selection, data reduction, and finally analyzing the HOTS data collected. From the data analysis, there obtained 9% with 6 HOTS reading essay questions (C4:2, C5:4) in English textbook of X grade, 6% with 7 HOTS reading essay questions (C4:5, C5:2) in English textbook of XI grade, and 10% with 12 HOTS reading essay questions (C5:12) in English textbook of XII grade. These factual results recommend all English teachers to be selective in utilizing English textbook due to improving studentsâ€™ critical thoughts. Also, the researcher suggests the further researcher to investigate HOTS effects on studentsâ€™ achievement.Keywords: Â Reading, Essay Task, HOTS